Prenatally Diagnosed Ureteropelvic Junction Obstruction in Three Siblings of one Family: A Case Report - Beksaç, Sinan; Balcı, Sevim; Yapıcı, Zuhal; Özyüncü, Özgür (Gynecology Obstetrics & Reproductive Medicine, 2008)
Ureteropelvic junction obstruction is a rare congenital abnormality. The mode of inheritance is thought to be autosomal dominant with variable expressivity. Here, a consanguineous family whose three siblings diagnosed to have various degree of ureteropelvic junction obstruction is presented. Ureteropelvic junction obstruction may have a genetic background and may recur in subsequent pregnancies. Furthermore, genetic thrombophilias may be associated with urinary abnormalities. Further molecular studies are necessary to prove that finding.